2007
DOI: 10.1074/jbc.m611809200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Cav3.3 T-type Calcium Channels by Gαq/11-coupled Muscarinic Acetylcholine Receptors

Abstract: T-type calcium channels play critical roles in controlling neuronal excitability, including the generation of complex spiking patterns and the modulation of synaptic plasticity, although the mechanisms and extent to which T-type Ca 2؉ channels are modulated by G-protein-coupled receptors (GPCRs) remain largely unexplored. To examine specific interactions between T-type Ca 2؉ channel subtypes and muscarinic acetylcholine receptors (mAChRS), the Cav3.1 (␣ 1G ), Cav3.2 (␣ 1H ), and Cav3.3 (␣ 1I ) T-type Ca 2؉ cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 66 publications
2
35
1
3
Order By: Relevance
“…1), potentiating Ca v 3.1 and Ca v 3.2 isoforms while inhibiting Ca v 3.3 T-type channels. The latter is consistent with the known inhibition of Ca v 3.3 channels by G␣ q/11 -coupled mAChRs (Hildebrand et al, 2007 . Inset, Representative EPSP recorded at the soma after PF stimulation.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…1), potentiating Ca v 3.1 and Ca v 3.2 isoforms while inhibiting Ca v 3.3 T-type channels. The latter is consistent with the known inhibition of Ca v 3.3 channels by G␣ q/11 -coupled mAChRs (Hildebrand et al, 2007 . Inset, Representative EPSP recorded at the soma after PF stimulation.…”
Section: Discussionsupporting
confidence: 77%
“…The Ca v 3.2 isoform is regulated by G␤ 2 ␥-proteins, CAMKII, and redox changes (Welsby et al, 2003;Wolfe et al, 2003;Joksovic et al, 2006), whereas G␣ q/11 -coupled muscarinic acetylcholine receptors (mAChRs) inhibit Ca v 3.3 channels but not Ca v 3.1 or Ca v 3.2 channels (Hildebrand et al, 2007). Hence, T-type channel function may be finely tuned in various cell types according to the combined repertoire of channel isoforms and modulatory pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4, D-F) is consistent with other studies in which PMA and other activators of PKC (i.e., 1-oleoyl-2-acetyl-sn-glycerol, phorbol-12,13-dibutyrate, and phorbol- 12,13-didecanoate) inhibited natively expressed T-type currents in neuronal (Marchetti and Brown, 1988;Schroeder et al, 1990;Cheong et al, 2008) and non-neuronal cells . However, our data are also in contrast with studies in which Ca V 3.2 channels were either unaffected (Park et al, 2003) or were significantly stimulated by PMA (Park et al, 2003Hildebrand et al, 2007). It is also interesting to mention the temperature-dependence of PMA effects.…”
Section: Nk1 Receptor Modulates Ca V 32 207contrasting
confidence: 55%
“…Three T-channel subunits have been identified: Cav3.1, Cav3.2, and Cav3.3 (Perez-Reyes, 2003), which are implicated in distinct physiological functions, as recently supported by knock-out (KO) mice studies (Kim et al, 2001;Chen et al, 2003;Lee et al, 2004;Mangoni et al, 2006;Choi et al, 2007). Over the past few years, intracellular messenger pathways (Wolfe et al, 2003;Chemin et al, 2006;Park et al, 2006;Chemin et al, 2007b;Hildebrand et al, 2007;Iftinca et al, 2007;Tao et al, 2008) and endogenous ligands (Nelson et al, 2007a,b;Traboulsie et al, 2007;Maeda et al, 2009) regulating Cav3 activity were identified, including bioactive lipids (Chemin et al, 2001(Chemin et al, , 2007aRoss et al, 2008Ross et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%